Volunteers for the Revolution : The International Militia of the POUM in the Spanish Civil War - Durgan, Andy (Historical Materialism Book Series, 2026)
That thousands of members of the International Brigades fought heroically against fascism during the Spanish Civil War is well known. Far less known-aside from the notable exception of George Orwell-is the presence of five hundred foreign combatants in the militias of the anti-Stalinist Partido Obrero de Unificación Marxista (POUM). This book provides, for the first time, an exhaustive study of these volunteers: their socio-political background, their participation in the Civil War and revolution, their role as victims of Stalinist slander and repression, and their fate during the Second World War and beyond.